The impact of super-absorbent materials on the thermo-physiological properties of textiles. Issue 6 (April 2015) - Houshyar, Shadi; Padhye, Rajiv; Vijayan, Arun; Jadhav, Amit; Ranjan, Sandip
The use of appropriate protective clothing systems in high-risk environments is absolutely essential. Such protective clothing may not provide the desired wearer comfort due to the complexities associated with the system. These constraints are largely due to the multiple layers involved in the protective ensemble. Firefighters' protective clothing systems, in particular, have limited or no water vapor permeability. This prevents evaporative heat loss and leads to thermal strain and sweat accumulation. This accumulated sweat on the skin and on the internal layer close to the body causes considerable discomfort to the user due to the sensation of wetness. Extensive research has been done to improve the comfort properties of such protective clothing. This research adds yet another dimension where a new inner-layer construction has been developed with high liquid and vapor-absorption capacity that could assist in keeping the moisture and vapor away from the skin and, in addition, retain a dry microclimate close to the skin. The developed materials were tested for their biophysical properties that included tests such as thermal and water vapor resistance, air permeability and moisture management properties. Experimental results in this study indicated that super-absorbent materials, when incorporated into a woven textile material, showed enhanced wearer comfort. It was observed that these super-absorbent materials have the capability to quickly wick the moisture away from the body and, in doing so, have the tendency to keep the skin dry.